Territorial management and environmental zoning in the Coruripe-AL River Basin: territorial clashes and geographical perspectives - Sandoval Dias Duarte; José Lidemberg de Sousa Lopes (Universidade Estadual de Alagoas, 2021)
This article is the result of an excerpt from the master's dissertation defended in March 2020 in the Program in Territorial Dynamics and Culture (PRODIC) of the State University of Alagoas-Uneal, which has as its object of study the Hydrographic Basin of Rio Coruripe-AL. Environmental zoning is presented at the expense of land use and occupation, based on the appropriation of natural resources in a hydrographic basin, as it constitutes a factor of analysis and territorial management instrument in the context of the geoenvironmental characteristics that a hydrographic basin may present, due to systematize the main activities developed in the socio-environmental field, enhancing socioeconomic development, with a focus on territorial planning and management. This study proposesan ecological-economic zoning (ZEE), embedded within the meaning of Decree 4.297 / 2002 and others in the light of human and environmental rights, based on instruments adopted in the characterization of theCoruripe River Basin (BHRC) in Alagoas, based onin the geographic perception of the existing natural resources. For this purpose, the study had as methodological parameter and concepts addressed, works carried out on Hydrographic Basins, such as: Carvalho (2006), Cunico (2007), Pereira (2010), Lopes (2013), Peres (2016), Santos (2018), Jacó (2019), among others. To identify the socio-environmental impacts, images obtained via satellite were initially used to make maps prepared by the Qgis software, in which the use and occupation of the soil is emphasized in BHRC, bringing areas of prominence due to their anthropization by the use of lands. The Coruripe River Basin, in turn, presents a variation of crops, distributed in the more than 19 municipalities where its beds and banks extend. For such an analysis of the misuse of the lands, the natural elements were analyzed: geolology and geomorphology. These were influenced, consubstantially, by the topography and by geoclimatic and anthropic factors. The main problems of socioenvironmental impacts are necessarily due to the emission of solid waste, sewage in natura thrown into the river and the tributaries, pasture in the breeding of cattle and trampling in areas close to the springs,crops in use of river waters,silting up the springs, all of which indicate BHRC's socio-environmental vulnerability.